Pendidikan sebagai Hak Asasi Manusia: Analisis Dampak terhadap Perubahan Sosial dan Sistem Hukum Pendidikan di Indonesia - Dedi Mulyadi; Sani San Zein; Widiya Meynuary; Feyza Ashila Putri Hidayat; Prima Satria Kusumah; Farhan Dwi Kurnia; Yasser Kahfi (Al-Musthalah: Jurnal Riset dan Penelitian Multidisiplin, 2024)
This article discusses the application of Education as a Human Right. Human Rights are fundamental human rights that refer to the dignity and worth of God Almighty's creation, which are innate from birth and cannot be violated or abolished by anyone. Education as a human right means that everyone has the right to the supremacy of law without discrimination. Thus, the state is obliged to protect, respect and fulfill its right to education. Based on Law Nomor 20 of 2003 concerning the national education system, there is a government obligation to fulfill the right to education. This obligation means that the state is responsible for providing free and mandatory basic education for school-aged children. This obligation also requires the central and regional governments to be responsible for efforts to make the nation's life smarter which will have a good social impact on society